Pharmacological Treatment of Schizophrenia: Japanese Expert Consensus - Sakurai, Hitoshi; Yasui-Furukori, Norio; Suzuki, Takefumi; Uchida, Hiroyuki; Baba, Hajime; Watanabe, Koichiro; Inada, Ken; Kikuchi, Yuka Sugawara; Kikuchi, Toshiaki; Katsuki, Asuka; Kishida, Ikuko; Kato, Masaki (Pharmacopsychiatry, 2021)
Introduction Conventional treatment guidelines of schizophrenia do not necessarily provide solutions on clinically important issues.Methods A total of 141 certified psychiatrists of the Japanese Society of Clinical Neuropsychopharmacology evaluated treatment options regarding 19 clinically relevant situations in the treatment of schizophrenia with a 9-point scale (1=“disagree” and 9=“agree”).Results First-line antipsychotics varied depending on predominant symptoms: risperidone (mean±standard deviation score, 7.9±1.4), olanzapine (7.5±1.6), and aripiprazole (6.9±1.9) were more likely selected for positive symptoms; aripiprazole (7.6±1.6) for negative symptoms; aripiprazole (7.3±1.9), olanzapine (7.2±1.9), and quetiapine (6.9±1.9) for depression and anxiety; and olanzapine (7.9±1.5) and risperidone (7.5±1.5) for excitement and aggression. While only aripiprazole was categorized as a first-line treatment for relapse prevention (7.6±1.0) in patients without noticeable symptoms, aripiprazole (8.0±1.6) and brexpiprazole (6.9±2.3) were categorized as such for social integration. First-line treatments in patients who are vulnerable to extrapyramidal symptoms include quetiapine (7.5±2.0) and aripiprazole (6.9±2.1).Discussion These clinical recommendations represent the expert consensus on the use of a particular antipsychotic medication for a particular situation, filling a current gap in the literature.
Keywords: antipsychotics; expert consensus; pharmacotherapy; schizophrenia